Aromatic Alkylammonium Spacer Cations for Efficient Two‐Dimensional Perovskite Solar Cells with Enhanced Moisture and Thermal Stability. Issue 4 (6th February 2018) - Thrithamarassery Gangadharan, Deepak; Han, Yujie; Dubey, Ashish; Gao, Xinyu; Sun, Baoquan; Qiao, Qiquan; Izquierdo, Ricardo; Ma, Dongling
Abstract : Three‐dimensional (3D) perovskite solar cells are prone to degradation in the presence of moisture, heat, and light. Recently, two‐dimensional (2D) perovskites are synthesized by isolating metal halide perovskite layers using aliphatic or aromatic alkylammonium spacer cation, which can retain their performance under ambient humidity levels due to the hydrophobic property of the spacer cation. However, the best 2D perovskite thus far, using aliphatic short butylammonium (BA) cation as spacer cation, shows only a modest tolerance against moisture and heat due to the inferior hydrophobicity as well as the relatively smaller size of the BA cation. Here, a bulkier aromatic phenylethylammonium (PEA) used as a spacer cation to synthesis 2D perovksite in order to achieve highly stable solar cells. By modifying the crystallization process, an average power conversion efficiency (PCE) of 5.50% is achieved, which is the highest reported PCE for aromatic alkylammonium‐based lower dimensional perovskite solar cells. Importantly, unencapsulated (PEA)2 (MA)3 Pb4 I13 devices show enhanced moisture stability compared to other reported perovskite solar cells in harsh moisture environment (72 ± 2% relative humidity). Moreover, the use of organic materials in p‐i‐n type device, instead of metal oxides, as electron and hole extraction layers also paves the way toward constructing flexible perovskite solar cells. Abstract : Highly stable and efficient two‐dimensional (2D) perovskite solar cells are fabricated by modifying the solution deposition process. The modification of deposition process enhances the efficiency of C6 H5 (CH2 )2 NH3 )2 (CH3 NH3 )3 Pb4 I13 perovskite solar cell by ≈28% with respect to the conventional deposition. This study presents a comprehensive investigation of moisture and thermal stability of 2D perovskites, synthesized using large aromatic alkylammonium as spacer cation.